(untitled) (Acta Scientiarum. Biological Sciences, 2021)
The diversity of hawkmoths (Lepidoptera: Sphingidae) is poorly known in the biomes of the Bahia state. However, studies were carried out in other states of the northeastern region with species inventories in the Atlantic Forest, Caatinga and Cerrado. In order to bro aden the knowledge on of the richness and diversity of hawkmoths in the Atlantic Forest of the state of Bahia, six monthly sampling sessions were carried out in the State Ecological Station of Wenceslau Guimarães. Hawkmoths were captured using a 250-watt mercury-vapor light trap set against a white cloth panel, for two nights a month, between 6:00 p.m. and 6:00 a.m. A total of 266 specimens were collected, distributed across 17 genera and 41 species. The most abundant and dominant species were Isognathus swainsoni C. Felder, 1862, with a relative abundance of 12.41%, and Xylophanes amadis (Cramer, 1782) and Xylophanes anubus (Cramer, 1777), both with 7.9%. Our study represents the second inventory of hawkmoths for the state, totaling 59 species known for the Atlantic Forest of Bahia. Isognathus excelsior (Boisduval, [1875]) and Manduca lucetius (Cramer, 1780) represented new records for the biome. The accumulated number of species indicates the need for further sampling in order to safely reach the curve asymptote.